2005
DOI: 10.1111/j.1525-1438.2005.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic malignant melanoma arising in a mature ovarian cystic teratoma: a case report and literature review

Abstract: Primary malignant melanoma arising inform the ovary is rare, with only 30 cases described in the literature to date. The case reported here occurred in a 19-year-old woman and was rapidly progressive, resulting in death only 37 days following initial presentation. Management of this case is discussed in the context of the other reported cases. Surgery, ranging from an ovarian cystectomy to a radical debulking procedure, has been the main treatment with adjuvant chemotherapy utilized in only 4 of the previous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Primary melanomas of the ovary are thought to arise by malignant transformation of an associated dermoid cyst or monodermal teratoma. McNeilage et al 20 have described the characteristics of 31 cases of melanoma originating from mature ovarian cystic teratoma reported from 1901 to 2002. Cases without cystic teratoma have also been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Primary melanomas of the ovary are thought to arise by malignant transformation of an associated dermoid cyst or monodermal teratoma. McNeilage et al 20 have described the characteristics of 31 cases of melanoma originating from mature ovarian cystic teratoma reported from 1901 to 2002. Cases without cystic teratoma have also been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…McNeilage et al [49] identified 31 cases of ovarian melanomas. Thirteen (43%) of the patients died of their disease within 18 months of diagnosis.…”
Section: Ovarian Melanomamentioning
confidence: 98%
“…A comprehensive literature review revealed 37 cases of malignant melanoma originating from ovary. The first case dates back to 1901 (6)(7)(8)(9)(10)(11)(12). Cronge and Wooduff accepted absence of an extra-ovarian focus of malignant melanoma, presence of a focus of malignant melanoma in the same ovary harboring teratoma, and showing melanocyte junctional activity as diagnostic criteria for a primary ovarian malignant melanoma (17).…”
Section: Discussionmentioning
confidence: 99%
“…Primary ovarian malignant melanoma was first reported in 1901 (5). A total of 37 cases have been reported so far in the english literature (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%